Lula of Brazil : The Story So Far - Bourne, Richard, 1940- (Book collections on Project MUSE., 2008)
Describes Lula's childhood hardships in an impoverished family, his days as a trade unionist, and the strike movement that brought down Brazil's military dictatorship. This book chronicles Lula's campaigns for the presidency of Brazil, his first term in office beginning in 2002, a corruption scandal, and his reelection in 2006.